2019
DOI: 10.29252/aassjournal.7.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants and Mixed Sport Disciplines: A Comparison among Soccer, Combat and Motorcycle Athletes

Abstract: Background. Soccer, combat sports and motorcycling have all been classified as mixed in terms of their metabolism predominance thus showing a common multifaceted nature of physical requirements, which include aerobic capacity, strength, endurance, power and agility. Objectives. The aim of the current study was to compare allelic and genotype frequencies of four well-known polymorphisms among athletes from different mixed sport disciplines in order to investigate genetic markers suitable for distinguishing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
4
0
3
Order By: Relevance
“…Genetic association researchers should consider following the recommendations of the STREGA statement in the future. Only three studies (Cocci et al, 2019;Lulinśka-Kuklik et al, 2019;Lulinśka-Kuklik et al, 2018) in this review stated they attempted to adhere to STREGA recommendations. This resulted in inconsistent study designs and scores that ranged from 59-100% adherence.…”
Section: Methodological Rigourmentioning
confidence: 99%
“…Genetic association researchers should consider following the recommendations of the STREGA statement in the future. Only three studies (Cocci et al, 2019;Lulinśka-Kuklik et al, 2019;Lulinśka-Kuklik et al, 2018) in this review stated they attempted to adhere to STREGA recommendations. This resulted in inconsistent study designs and scores that ranged from 59-100% adherence.…”
Section: Methodological Rigourmentioning
confidence: 99%
“…В данных условиях тренеры должны использовать эффективные методики повышения уровня физической и функциональной подготовленности атлетов, позволяющие отечественным борцам дзюдо успешно конкурировать с зарубежными дзюдоистами на международной арене. Результаты SJFT показывают, что дзюдоисты, использовавшие кроссфит-сессии, демонстрируют примерно одинаковый уровень специальной физической подготовленности с элитными зарубежными атлетами, практикующими силовые тренировки высокой мощности [15,19].…”
Section: организация и методы исследованияunclassified
“…Анализ научных данных указывает, что специалисты рекомендуют использовать периодические тренировки для развития специальной физической пригодности дзюдоистов длительностью от 8 до 20 недель [4] и более [10]. Ведущие иностранные ученые рекомендуют использовать высокоинтенсивные интервальные тренировки (HIIT) в практике подготовки единоборцев [8,12,19]. Комплексы HIIT в практике единоборств представляют собой выполнение в максимальном темпе различных силовых упражнений и приемов борьбы [9].…”
unclassified
See 1 more Smart Citation
“…10 Previous study has showed that adipocyte Metrnl controls insulin sensitivity by the peroxisome proliferator-activated receptor gamma (PPAR) pathway, acts as an insulin sensitizer and possibly a therapeutic target for insulin resistance. 11-13 Another report argued that up-regulation in peroxisome proliferator-activated receptor gamma coactivator-1 (PGC-1), as an important regulator that induces mitochondrial biogenesis and increases Metrnl in muscle tissue. Metrnl could also transmit the positive effects of PGC-1 to other tissues followed by an up-regulation.…”
Section: Dear Editormentioning
confidence: 99%